Playing with fractions on an Interactive floor application: An exploratory case study in the math classroom - Ioannou, Marianna; Ioannou, Andri (My University, 2018)
The notion that engaging the body brings additional value in learning has lead researchers in evaluating technology-enhanced, whole-body learning experiences. Yet, we still need compelling evidence for the applicability of relevant tools and methods in school classrooms. We conducted an exploratory case study with 20 elementary-school students using three interactive floor applications in a typical school setting. Results demonstrated positive emotions; yet, cognitive phenomena require more careful investigation.
Keywords: Technology-enhanced; Whole-body learning experiences; Interactive floor applications